2002
DOI: 10.1051/0004-6361:20011421
|View full text |Cite
|
Sign up to set email alerts
|

2-D multiline spectroscopy of the solar photosphere

Abstract: Abstract. The structure and dynamics of the photosphere are investigated, with time series of broadband and monochromatic images of quiet granulation, at the solar disk center. Images were acquired with the IPM observing mode at the THEMIS telescope. Velocity and line center intensity fields, derived from the observation of three different photospheric lines, are used to study velocity and intensity patterns at different heights in the photosphere. Automatic segmentation procedures are applied to velocity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 29 publications
11
42
0
1
Order By: Relevance
“…By studying the velocity response functions as in Caccin et al (1977) and Berrilli et al (2002), we found that the major contribution to the measured velocities in Fe I 709.04 nm line originates in a layer 100 km above the photospheric surface.…”
Section: Los Velocity Mapsmentioning
confidence: 95%
“…By studying the velocity response functions as in Caccin et al (1977) and Berrilli et al (2002), we found that the major contribution to the measured velocities in Fe I 709.04 nm line originates in a layer 100 km above the photospheric surface.…”
Section: Los Velocity Mapsmentioning
confidence: 95%
“…We extracted velocities at two different altitudes. A line chord of 16 pm was used to sample a layer around an altitude of 80 km (Altrock et al 1975;Berrilli et al 2002) and a second chord of 8 pm, deeper in the line, was used to sample the atmosphere around 190 km. In order to detect potential spurious effects associated with the artificial flat-fielding operation, an additional set of spectra was computed from images not flat-fielded (Fig.…”
Section: Vertical Velocity Fieldsmentioning
confidence: 99%
“…As is well known, granulation with a typical 1-Mm size and 5-min lifetime are ubiquitous in high-resolution photospheric images (e.g., Title et al 1989;Berrilli et al 2002;Jin et al 2009). Groups of theses granules tend to move in a systematic way, which is characterized by a cellular convective motion at scales of the order of 32 Mm (Leighton et al 1962).…”
Section: Introductionmentioning
confidence: 97%